Collaboration of Profile Matching and MCDM-AHP Methods on Employee Selection for Promotion - Akmaludin, Akmaludin; Sihombing , Erene Gernaria; Dewi, Linda Sari; Rinawati , Rinawati; Arisawati, Ester (Politeknik Ganesha Medan, 2022)
To give appreciation to every employee who has been able to understand the journey of the system in a company, it is appropriate to be given appreciation in the process of changing leadership and as a form of motivation for all employees in the company as a form of promotion. The promotion process must be carried out objectively, so that a good leadership change system can be seen as a strength in the company's survival for each period. The process of changing leadership through promotions is at the forefront of running a sustainable company. With so many employees, the biggest obstacle that often becomes crucial is how to select the leadership relay holder through promotions in the company that can be carried out objectively, thus a method is needed. worthy to be used as a benchmark for selecting employees in terms of promotion. There is a method that can be used for employee selection as a form of promotion, namely the profile matching method through the assessment of the weight of the Aspects and the magnitude of the GAP value with the concept of determining the largest rank as the winner in the selection process for promoted employees. Of the six employees who are appointed as candidates for leadership candidates through promotions, they will be selected consistently with a number of criteria as a barometer of the selection process. The results obtained through the promotion of positions in the leadership change process were the first rank was elected KR02 (4.67), followed by the second rank KR01 (4.65) and the third rank KR05 (4.46). Thus, it can be said that the combination of profile matching and MCDM-AHP methods can be used to carry out the employee selection process as a form of promotion.